NURSING STUDENTS’ KNOWLEDGE REGARDING POST-MASTECTOMY EXERCISES IN ONCOLOGY UNITS AT THE UNIVERSITY – SUDAN - Aish Yousif Omer Alhussein; Omnia Hamed Alamin Idriss; Omnia Adel Ahmed Hussin; Amira Ibrahim Shames al Deen Mattar; Omaima Mohammed Abdallha Mohammed; Amna Awad Mohammed Ali; Ashraf Aldaw Oteiba Hammad; Alaa Amer Omar Abobakr; Sulafa Ali Salama Elehaimir (Universitas Airlangga, 2026)
Introduction: Breast cancer has one of the highest incidence and mortality rates among malignancies in women worldwide. Mastectomy, the surgical removal of breast tissue, remains a common treatment modality for breast cancer, and post-mastectomy exercises are essential for preventing complications such as lymphedema, improving mobility, and enhancing recovery in breast cancer patients. This study aims to assess nursing students’ knowledge regarding post-mastectomy exercises at the University of Health Sciences. Methods: This descriptive exploratory cross-sectional study assessed the knowledge of 100 nursing students at the University of Health Sciences regarding post-mastectomy exercises. Data were collected using a self-administered questionnaire and analyzed using SPSS version 20. Results: The students demonstrated an average knowledge level of 63% regarding lymphedema and post-mastectomy exercises. Second-year students exhibited the highest proportion of good knowledge (76.9%), substantially exceeding third-year (62.5%) and fourth-year students (37.7%). This finding challenges the effectiveness of a linear curriculum model and supports the need for a spiral curriculum, in which key concepts are revisited at progressively deeper levels throughout the program. The main barriers to learning were limited clinical exposure (53%) and lack of educational materials (46%), indicating that practical training requires review, development, and technical enhancement to achieve its intended goals. Conclusions: Nursing students’ knowledge of post-mastectomy exercises is inadequate, and both educational and clinical training designs require urgent revision. Innovative, reinforced, and interactive approaches are essential to equip future nurses with the competencies needed for effective post-mastectomy care.